CHEMICAL COMPOSITION AND BIOLOGICAL ACTIVITY OF CALOGAYA DESIPIENS LICHEN ABSTRACT - Professor A.A. Ibragimov; Odilova Nodirabegim Ikhtiyorjon qizi (Modern American Journals, 2025)
Calogaya desipiens is a lichen species belonging to the family Teloschistaceae, widely distributed across various ecosystems. This comprehensive review examines the chemical composition and diverse biological activities of C. desipiens, highlighting its potential pharmacological applications. Through systematic analysis of available scientific literature, we identified and categorized the lichen's secondary metabolites, including depsides, depsidones, anthraquinones, and dibenzofurans. The biological activities investigated encompass antimicrobial, antioxidant, anticancer, anti-inflammatory, and cytotoxic properties. Our findings demonstrate that C. desipiens exhibits significant bioactive potential, particularly against Gram-positive bacteria (with inhibition zones ranging from 12-25 mm) and free radicals (showing DPPH radical scavenging activity with IC50 values of 15-45 μg/mL). The anticancer activity against various cell lines, including MCF-7 and HeLa, revealed promising results with IC50 values between 20-80 μg/mL. This review consolidates current knowledge on C. desipiens while identifying research gaps and future directions for exploring this lichen's pharmaceutical potential. The findings support the traditional use of lichens in medicine and provide a scientific basis for further drug discovery efforts.
Keywords: Calogaya desipiens, lichen metabolites, biological activity, antimicrobial, antioxidant, anticancer, phytochemistry, natural products, drug discovery